Istihsan dan Aplikasinya dalam Inovasi Keuangan Syari’ah Kontemporer - Aditya, M Septian; Darmawati; Ahmad Rijali (Institut Muslim Cendekia, 2026)
Rapid technological and institutional transformations in the global financial system have generated complex transactional models that were unknown in classical Islamic jurisprudence. This phenomenon challenges Islamic legal methodology to maintain its normative authority while remaining responsive to socio-economic changes. This study examines istihsan as a flexible legal reasoning tool within Islamic legal theory and evaluates its practical relevance in contemporary Islamic finance. Using qualitative library research, this study analyzes classical ushul fiqh literature and contemporary Islamic finance fatwas. The study finds that istihsan functions as a methodological mechanism that enables jurists to depart from strict analogical reasoning (qiyas) toward stronger legal evidence to achieve public welfare (maslahah) and prevent hardship (masyaqqah). In practice, the principles of istihsan underpin the legality of various modern financial innovations, such as parallel salam financing in Islamic banking, digital transactions without verbal offer and acceptance (click-contracts and QR codes) in the fintech sector, self-service systems in modern trade, and collective risk management in Islamic insurance. This study argues that istihsan plays a pivotal role as a methodological bridge connecting classical jurisprudence with the needs of modern financial innovation to ensure the sustainability of the Islamic financial ecosystem.